Ozone air quality deteriorated by inter-provincial transport downwind of Seoul metropolitan area - Kim, Taehee; Choi, Dongwon; Ko, Wonseok; Kim, Yujeong; Kim, Jimin; Kwak, Kyung Hwan; Kang, Yoon Hee; Kim, Soontae (Atmospheric Environment, 2023)
While ozone air quality has continuously improved in major cities worldwide, it has recently degraded in cities in East Asia, including South Korea. This study aims to examine one possible mechanism for an ozone episode during the summertime that is the deteriorated air quality by inter-provincial transport. We analyzed an ozone episode that occurred in the Seoul metropolitan area and its surrounding areas during early summer. We used the Community Multiscale Air Quality (CMAQ) model, employing the Process Analysis (PA) method, to estimate the contributions of inter-provincial transport of ozone and its precursors from the metropolitan area to downwind cities. First of all, the observation data showed that the daily maximum 1-h average ozone (O3) concentrations in the surrounding cities exceeded 100 ppb for at least three consecutive days from June 2nd to 6th, 2019. In the cluster analysis of diurnal patterns, it was evident that the daily maximum O3 concentration increased from the metropolitan area to the downwind cities, with peak times occurred up to 2-h later. In the PA results of surface O3 concentration in the CMAQ simulations, a significant downward diffusion of ozone was observed in Seoul during the daytime due to the strong chemical reduction of ozone (i.e., NO titration). On the other hand, Chuncheon and Wonju, the major downwind cities, exhibited a significant positive contribution of vertical transport to surface O3 concentration as the boundary layer develops in the morning. The ozone in the residual layer at night was primarily produced in the metropolitan area and, then, transported to downwind cities through inter-provincial transport. Consequently, this implies that the inter-provincial transport of ozone in the atmospheric boundary layer plays an important role in the formation of a multi-day ozone episode in the downwind cities of metropolitan area.
Keywords: Community multi-scale air quality models; East Asia; Inter-provincial transport; Major cities; Metropolitan area; Ozone episodes; Process analysis; Residual layers; Seoul metropolitan area; WRF-community multiscale air quality model; Inter-provincial transport; Ozone; Process analysis; Residual layer; WRF-CMAQ model